2016
DOI: 10.1016/j.gaceta.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early childhood caries in Chile

Abstract: The high prevalence of caries in this young group is concerning. The factors associated with caries identified in this study could help in the design of preventive interventions at early ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
18

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 10 publications
2
26
0
18
Order By: Relevance
“…3 A recent oral health study conducted in preschoolers in the south of Chile reported a prevalence of 20.3% in 2-year-olds and 52.7% in 4-year-olds. 4 The study also revealed more severe ECC in children of lower socioeconomic status, a factor widely analyzed in the literature. 2,[5][6][7] Higher caries prevalence has been reported in rural preschoolers in previous studies, establishing an association between caries and the condition of rurality.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…3 A recent oral health study conducted in preschoolers in the south of Chile reported a prevalence of 20.3% in 2-year-olds and 52.7% in 4-year-olds. 4 The study also revealed more severe ECC in children of lower socioeconomic status, a factor widely analyzed in the literature. 2,[5][6][7] Higher caries prevalence has been reported in rural preschoolers in previous studies, establishing an association between caries and the condition of rurality.…”
Section: Introductionmentioning
confidence: 58%
“…The group categorized as FONASA A had a higher mean dmft index. Hoffmeister et al 4 also significantly associated ECC with low socioeconomic status, but in an urban Chilean population. Global evidence confirms that socioeconomic status is a factor for ECC.…”
Section: Discussionmentioning
confidence: 90%
“…En Chile, la caries dental se expresa desde un 16,8% a los dos años edad hasta un 100% en la edad adulta. Un estudio realizado en la zona sur del país, en el marco de la construcción del diagnóstico de salud bucal de la población preescolar, concluye que se observan altas prevalencias de caries en edades muy tempranas, que la posición socioeconómica se encuentra asociada a la experiencia de caries y que los hábitos de nutrición se encuentran relacionados con el desarrollo de la enfermedad en todos los niveles socioeconómicos (24) . De los pocos estudios epidemiológicos existentes, se advierte una alta prevalencia de caries a los 12 años de edad, con un 62,5% y un promedio de 1,9 dientes afectados por caries (25) .…”
Section: Discussionunclassified
“…Although its global prevalence has decreased over recent decades, ECC continues to be a serious public health problem in certain populations, particularly in developing countries and unprotected subgroups in industrialized nations such as immigrants, ethnic minorities or rural communities where the prevalence in the literature is as high as 90% . In Chile, the reported prevalence ranges from 8% to 88%, depending on the diagnostic criteria used …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In Chile, the reported prevalence ranges from 8% to 88%, depending on the diagnostic criteria used. 4,5 Living in a rural environment is an important risk factor for ECC because of the associated low socioeconomic status, poor dietary habits, low maternal educational levels and relatively poor access to fluoridated water or dental services. 2,6,7 The high prevalence of ECC in rural communities without access to fluoridated water has a series of consequences, such as hospitalization and emergency care for caries complications, which affects the quality of life of the preschoolers involved.…”
Section: Introductionmentioning
confidence: 99%